LITERATURE REVIEW: THE IMPACT OF WORK STRESS, WORKLOAD, AND WORK ENVIRONMENT ON EMPLOYEE’S TURNOVER INTENTION IN INDONESIA - Khoir, Oktario Dinansa; Dwiyanti, Endang; Mandagi, Ayik Mirayanti; Alfayad, Afan (Journal of Community Mental Health and Public Policy, 2024)
Background: Employee turnover intention is a significant challenge for organizations, impacting productivity and operational costs. Understanding its contributing factors is crucial for effective human resource management. Purpose: To analyze the influence of work stress, workload, and work environment on employee turnover intention across various sectors in Indonesia. Methods: A systematic review of research articles published between 2020 and 2022 was conducted using the PRISMA-P approach. Literature research was performed through electronic databases using predefined keywords. Results: Work stress and workload generally showed significant positive effects on turnover intention (p < 0.05 in most studies). Work environment typically demonstrated a significant negative effect (p < 0.05), with one exception. Simultaneous analysis revealed substantial contributions of these factors to turnover intention, with an explained variance reaching up to 75.2%. One study found a non-significant negative relationship between work stress and turnover intention, highlighting the complexity of these relationships. Conclusion: Work stress, workload, and work environment significantly influence employee turnover intention, though effects may vary across contexts. A comprehensive approach in human resource management, focusing on these factors, is crucial for enhancing employee retention and organizational productivity. Abstrak Latar belakang: Turnover intention karyawan merupakan tantangan signifikan bagi organisasi, berdampak pada produktivitas dan biaya operasional. Memahami faktor-faktor yang berkontribusi sangat penting untuk manajemen sumber daya manusia yang efektif. Tujuan: Menganalisis pengaruh stres kerja, beban kerja, dan lingkungan kerja terhadap turnover intention karyawan di berbagai sektor di Indonesia. Metode: Tinjauan sistematis terhadap enam artikel penelitian yang dipublikasikan antara tahun 2020 dan 2022 dilakukan menggunakan pendekatan PRISMA-P. Pencarian literatur dilaksanakan melalui basis data elektronik menggunakan kata kunci yang telah ditentukan. Hasil: Stres kerja dan beban kerja umumnya menunjukkan pengaruh positif yang signifikan terhadap turnover intention (p < 0,05 pada sebagian besar studi). Lingkungan kerja biasanya menunjukkan pengaruh negatif yang signifikan (p < 0,05), dengan satu pengecualian. Analisis simultan mengungkapkan kontribusi substansial dari faktor-faktor ini terhadap turnover intention, dengan varians yang dijelaskan mencapai 75,2%. Satu studi menemukan hubungan negatif yang tidak signifikan antara stres kerja dan turnover intention, menunjukkan kompleksitas hubungan ini. Kesimpulan: Stres kerja, beban kerja, dan lingkungan kerja secara signifikan mempengaruhi turnover intention karyawan, meskipun efeknya dapat bervariasi antar konteks. Pendekatan komprehensif dalam manajemen SDM yang berfokus pada faktor-faktor ini sangat penting untuk meningkatkan retensi karyawan dan produktivitas organisasi.